The Use of kenaf Fiber Reinforced Polymer to confine the concrete cylinder - Mahjoub, R. (Elsevier Ltd, 2016)
Recently, Fiber Reinforced Polymer (FRP) wrapping technique has been used as an alternative to retrofit concrete members especially in columns. FRPs based on natural fibers are new materials used in wrapping technique and are an alternative to synthetic fibers. The ability of bio-composites as an element to wrap concrete columns was studied in this study. This research is a laboratory experiment conducted on the performance of concrete columns subjected to axial compressive load. Many samples of plain concrete cylinders were prepared for testing which consists of unwrapped samples, samples wrapped with glass FRP and Kenaf FRP.